1999
DOI: 10.1088/0031-9155/44/9/309
|View full text |Cite
|
Sign up to set email alerts
|

An EGS4-ready tomographic computational model of a 14-year-old female torso for calculating organ doses from CT examinations

Abstract: Fifty-four consecutive CT scans have been used to construct a tomographic computational model of a 14-year-old female torso suitable for the determination of organ doses from CT. The model, known as ADELAIDE, is in the form of an input file compatible with user codes based on XYZDOS.MOR from the readily available EGS4 Monte Carlo radiation transport code. ADELAIDE's dimensions are close to the Australian averages for her age so the model is representative of a 14-year-old girl. The realistic anatomy in the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 18 publications
0
62
0
1
Order By: Relevance
“…Caon et al ( 61 ) reported on a CT dosimetry study for a 14‐year‐old female tomographic phantom. The EGS4 radiation transport code was used for Monte Carlo simulation of a GE Hi‐Speed Advantage CT scanner operating at 120 kVp with 10 mm beam width.…”
Section: Discussionmentioning
confidence: 99%
“…Caon et al ( 61 ) reported on a CT dosimetry study for a 14‐year‐old female tomographic phantom. The EGS4 radiation transport code was used for Monte Carlo simulation of a GE Hi‐Speed Advantage CT scanner operating at 120 kVp with 10 mm beam width.…”
Section: Discussionmentioning
confidence: 99%
“…The images have a pixel size of 2.53 × 2.53mm and slice separation of 10mm. The data set is referred to as ADELAIDE [1].…”
Section: Data Setmentioning
confidence: 99%
“…Models of human anatomy are required in order to allow the calculation of organ doses and effective dose received from diagnostic radiography procedures such as computed tomography [1]. The cross-sectional (tomographical) medical images produced by medical imaging are a source of data for constructing models of human anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…More phantoms were developed like the NORMAN one (for NORmal MAN) of the National Radiological Protection Board (Dimbylow, 1998), and the one of Zubal (Zubal et al, 1994). ADELAIDE (Caon et al, 1999), GOLEM (Zankl et al, 2001), developed by Zankl and Wittmann are also voxel phantoms, same for FAX (Kramer et al, 2003) and MAX (Kramer et al, 2004) that were made to fit the ICRP Publication 89 (ICRP, 2002) recommendations regarding organs weights. VIP-Man created by Xu (Xu et al, 2000) and the Canine Anatomic Phantom designed by Padilla (Padilla et al, 2008).…”
Section: A Survey Of Voxelized Phantomsmentioning
confidence: 99%